2015
DOI: 10.1177/0009922815570618
|View full text |Cite
|
Sign up to set email alerts
|

Cholestatic Hepatitis Induced by Epstein-Barr Virus in a Pediatric Population

Abstract: EBV infection should be included in the differential diagnosis of CH in all age groups. In the vast majority, full recovery is expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 21 publications
0
30
0
9
Order By: Relevance
“…7 Cholestatic hepatitis is a rare sequelae of EBV, and jaundice is seldom reported; however, it is more frequent in people aged 35 and older. 12,13,14 If seen, jaundice may be due to autoimmune hemolytic anemia, cholestasis due to acalculous cholecystitis, biliary duct obstruction due to abdominal lymphadenopathy, or cholestatic hepatitis. 9,15 The pathogenesis of cholestatic hepatitis due to EBV is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…7 Cholestatic hepatitis is a rare sequelae of EBV, and jaundice is seldom reported; however, it is more frequent in people aged 35 and older. 12,13,14 If seen, jaundice may be due to autoimmune hemolytic anemia, cholestasis due to acalculous cholecystitis, biliary duct obstruction due to abdominal lymphadenopathy, or cholestatic hepatitis. 9,15 The pathogenesis of cholestatic hepatitis due to EBV is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Studies of pediatric cases of EBV hepatitis revealed gallbladder wall thickening in 45-50%. 18,19 From authors review of the literature, the majority of patients presenting with acute symptomatic EBV hepatitis, without infectious mononucleosis syndrome, have normal biliary tree imaging without dilation. 5,20,21 In one case report, a patient had a mildly dilated common bile duct at 9 mm and underwent ERCP to exclude biliary obstruction, which revealed no abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…O VEB é um agente infecioso muito comum na população pediátrica, afetando por ano cerca de 345 -671/100 000 adolescentes. 7 A manifestação clínica clássica neste grupo etário é a MNI, 3,6,8,10 podendo surgir com outros sinais e sintomas como esplenomegália (> 50%), hepatomegália (30% -50%) e exantema (5%, 90% -100% nos casos tratados com ampicilina). 2 A icterícia, por sua vez, é uma manifestação rara da infeção a VEB, estando descrita em menos de 5% dos doentes em idade pediátrica.…”
Section: Discussionunclassified
“…2 A gravidade da sintomatologia está relacionada com a resposta imunológica, sendo a infeção habitualmente subclínica durante a infância e francamente sintomática durante a adolescência. 1,[4][5][6][7] Neste grupo etário pode manifestar-se como mononucleose infeciosa (MNI). 5,8 Inicialmente, existe um período prodrómico com astenia, anorexia e mialgias, e pode observar-se esplenomegália e/ou hepatomegália.…”
Section: Introductionunclassified